2015
DOI: 10.1055/s-0035-1557433
|View full text |Cite
|
Sign up to set email alerts
|

Delayed visual evoked potentials in children with Plasmodium falciparum malaria and reduced consciousness

Abstract: We aimed to investigate the visual evoked potential (VEP) in children unconscious with Plasmodium falciparum malaria, a common cause of death in Africa. Flash VEPs were carried out in Malawi during one peak malaria season. Children were included in the study if they had P. falciparum malaria and reduced consciousness ? Blantyre Coma Score (BCS) 4 or less out of 5. Initial VEPs were performed after stabilising the patient and commencing treatment. To investigate optimal VEP protocols, varying stimulus parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Beare, et al found papilledema prevalence of 15% in cerebral malaria [9]. Retinopathy was associated with subsequent death (relative risk, 3.7) and papilledema conferred the highest risk (RR-4.5) [10] . Lewallen found the relative risk of death in patients with papilledema was 6.7 times that in patients without papilledema and also found that patients with papilledema had poor outcome 5.2 times greater than those without this finding [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Beare, et al found papilledema prevalence of 15% in cerebral malaria [9]. Retinopathy was associated with subsequent death (relative risk, 3.7) and papilledema conferred the highest risk (RR-4.5) [10] . Lewallen found the relative risk of death in patients with papilledema was 6.7 times that in patients without papilledema and also found that patients with papilledema had poor outcome 5.2 times greater than those without this finding [11] .…”
Section: Discussionmentioning
confidence: 99%